Evaluation of the antiasthmatic properties of stems and leaves of Waltheria indica L. (Malvaceae): Focus on antioxidant and anti-inflammatory activity, and quantification of phenolic compounds - Zakaline Yabré; W. Leila Marie Esther Belem-Kabré; Rainatou Boly; Raogo Ouédraogo; Abdoul Gilchrist Laurent Boly; Tata Kadiatou Traoré; Noufou Ouédraogo; Estelle Noëla Hoho Youla (Elsevier, 2024)
Background: Waltheria indica L. (Malvaceae) has a long history of use in traditional medicine for treating inflammation and asthma. This study aimed to evaluate the antiasthmatic properties of the hydroethanolic extract derived from the stems and leaves of W. indica. Method: Phytochemical analysis was conducted using thin-layer chromatography, and phytoconstituents were quantified using appropriate techniques. The antioxidant activity was determined through DPPH radical scavenging, ABTS+ radical cation decolorization, ferric ion reduction, and lipid peroxidation inhibition. The fractions' acute general toxicity was assessed following the guidelines of OECD 423. The in vitro anti-inflammatory activity was evaluated by inhibiting the 15-lipoxygenase and phospholipase A2 (PLA2), while the in vivo evaluation involved carrageenan-induced paw edema in mice at doses of 100, 200, and 400 mg/kg of body weight (b.w.). Results: The study revealed a total phenolic content of 116.03 ± 1.02 mg TAE/g in the residual fraction and 146.62 ± 2.02 mg TAE/g in the hydroethanolic extract. The extract and fractions also exhibited significant flavonoid content. The fractions' lethal dose was estimated to equal 5000 mg/kg b.w. Furthermore, the extract and fractions demonstrated substantial antioxidant and anti-inflammatory effects. Conclusion: The observed pharmacological activities provide scientific evidence for the traditional medicinal use of the leafy stems of W. indica in treating asthma.